Selected determinants of production and sales of products in short food supply chains by farms keeping animals of native breeds - Matysik-Pejas, Renata (Wybrane uwarunkowania produkcji i sprzedaży towarów w krótkim łańcuchu dostaw żywności przez gospodarstwa zajmujące się hodowlą zwierząt ras rodzimych, 2020)
The aim of the study was to identify factors determining farms’ decision to produce and sell products obtained from animals of native breeds in short food supply chains. The empirical material was the result of a survey carried out in 2017. The direct interview method was used to collect information. The research sample included 144 farms keeping animals of native breeds of cattle, sheep and pigs. The spatial scope of the research covered three provinces of south-eastern Poland. The group of factors positively stimulating the development of food sales in short supply chains includes the knowledge and skills of breeders and the expected demand for products from the farms. In turn, the group of factors constituting obstacles and causing farms not to undertake this activity is connected with the necessary amount of work input, the need to develop a marketing concept for this activity and to create an appropriate image on the market, as well as veterinary, sanitary and tax regulations
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 8, s. 93-103